Safe at home. (American City & County, 2007)
This section offers news briefs related to home safety in the U.S. The Sandy Springs, Georgia Police Department has purchased records management and mobile computing software from SunGard HTE. The Jacksonville, Florida, Sheriff's Office has purchased electronic stun guns from TASER International. The Tempe, Arizona Fire Department has purchased daily planning and emergency mitigation software from locally based ESS.